Agronomic and physiological characteristics of high‐yielding ratoon rice varieties. (5th November 2021) - Zhang, Qiang; Liu, Xiangchen; Yu, Guilong; Wang, Hao; Feng, Daqing; Zhao, Haiying; Liu, Lijun
Abstract: To clarify the agronomic and physiological characteristics of high‐yielding ratoon rice varieties, 14 rice varieties representing two types (high yield in ratoon crop [RH] and low yield in ratoon crop [RL]) were used as experimental materials. Compared with RL, the grain/leaf ratio of RH at the full heading stage in the main crop was lower. Also, the leaf area duration, net assimilation rate (NAR), crop growth rate (CGR), dry matter weight, photosynthetic rate of flag leaf, and root oxidation activity from the full heading to maturity stage in the main crop were higher. The leaf area index (LAI) and dry matter weight at maturity in the main crop were higher in RH than RL, whereas the rates of LAI attenuation, dry matter translocation and dry matter translocation efficiency (DMTE) from full heading to maturity, and harvest index (HI) in the main crop were relatively lower. The CGR, NAR, dry matter weight from full heading to maturity, and dry matter weight and root oxidation activity at maturity in the main crop were significantly and positively correlated with the yield of the ratoon crop. The rate of LAI attenuation and DMTE from full heading to maturity, grain/leaf ratio at full heading, and HI in the main crop were significantly and negatively correlated with the yield of the ratoon crop. Rational utilization of these agronomic and physiological characteristics would be helpful to screening and breeding high‐yielding rice varieties for ratoon production. Core Ideas: The agronomic and physiological characteristics of high‐yielding ratoon rice are clarified. High‐yielding ratoon rice had low grain/leaf ratio at the full heading stage of the main crop. High‐yielding ratoon rice had strong photosynthetic capacity at the late growth stage of the main crop. High‐yielding ratoon rice had low dry matter translocation efficiency at maturity of the main crop. Leaves and roots were highly physiologically active at the late growth stage of the main crop.